The Therapeutic Exercise Alternative Those Benefit in Reducing Low Back Pain among Pregnant Mom: A Systematic Literature Review - Jannah, Roikhatul; Molina, Witri; Sariana, Erna; Sativani, Zahra (Ikatan Fisioterapi Indonesia, 2022)
Introduction: Low back pain is a local pain that often occurs in pregnant women and has an impact on the activities of pregnant women. This pain can be treated with exercise therapy. Exercise therapy is a systematic, planned performance of body movements, postures, or physical activities aimed at patients/clients with the aim of relieving symptoms and improving health-related physical functions. Objective: This study aims to determine the various types of exercise therapy used to reduce low back pain in pregnant women. Methods: The research method is a systematic literature study with data collection using 3 search engines namely Pubmed, Google Scholar, and Semantic Scholar and then identified using initial selection instruments, methodological selection and data extraction. Results: There were 8 eligible literatures and overall there were significant results from giving exercises therapy to reduce the intensity of low back pain. The exercise therapy provided is in the form of stabilization exercise, stretching exercise, strengthening exercise, aerobic exercise, pelvic floor exercise, antenatal exercise, yoga exercise, and pilates exercise. The measuring instruments used are VAS and NRS. Conclusion: Exercise therapy can be given to pregnant women to reduce the intensity of low back pain. Further research needs to establish appropriate, reliable and valid pain intensity outcome measures to see which exercise is more beneficial for low back pain during pregnancy.